3D measurements of micro‐objects based on monocular wide‐field optical microscopy with extended depth of field. Issue 12 (23rd October 2018) - Qu, Yufu; Zhang, Ping; Hu, Yongbo
Abstract: Monocular rotational microscopes suffer from shallow depth of field and reduced field of view. Consequently, we propose monocular wide‐field optical microscopy with extended depth of field to enable accurate 3D measurements of micro‐objects. We use a liquid lens and a 4f system to extend the system's depth of field and two additional rotational reflectors to capture multi‐view image sequences. In addition, we increase the number of expansion directions in the patch‐based multi‐view stereo algorithm and optimize the expansion radius. Our approach outperforms that based on the patch‐based multi‐view stereo method and achieves a high relative measurement accuracy of 1.9%. Research Highlights: This study proposes 3D measurements of micro‐objects via monocular rotational microscopy. The depth of field is extended by the use of a liquid lens and a 4f system. Our approach outperforms that based on the patch‐based multi‐view stereo method and achieves a high relative measurement accuracy of 1.9%. Abstract :